Does firm value matter for corporate disclosure? A study of Covid-19-related disclosure by Vietnamese listed firms - Hoàng Thị Thanh Thanh; Nguyễn Hữu Cường (Tạp chí Khoa học và Công nghệ, 2023)
Existing research has explored the relationship between firm value and corporate disclosure, but little is known about this association during the COVID-19 pandemic and ensuing economic crisis. This study investigates whether firm value influences corporate disclosure in the Vietnamese stock market in 2021, the second year of the pandemic. Using Tobin's Q as a measure of firm value and COVID-19-related disclosure as a proxy for corporate disclosure, a regression model is employed. Control variables capturing the firm's profile and internal corporate governance are included. The sample consists of the top 100 Vietnamese listed firms by market capitalization in 2021. The findings reveal a negative impact of firm value on corporate disclosure, indicating that a firm's market evaluation can influence its decision to disclose information during a pandemic-induced economic crisis.